Challenges of colorectal cancer screening in patients with learning disabilities: the way forward - Ahmed, Zeeshan; Ehsan, Aisha; Passmore, Jacqueline; Akingboye, Akifemi (Journal of Health Inequalities, 2022)
People with learning disabilities (LD) are now living longer; thus, the incidence of cancer within this population is increasing. Available data indicate an excess of digestive tract cancers in people with LD, but colorectal cancer has rarely been specifically studied or extensively reviewed. This is despite risk factors such as being overweight, obesity, and lack of exercise being more frequent in people with LD. Published data showed that the frequency trends slightly higher than that found in the general population. Screening presents a unique opportunity to discover early colorectal cancer, but it is an underused utility in people with LD compared to the general population due to multiple reasons. Furthermore, the clinical presentation is frequently masked, particularly by challenging behaviours, and colorectal cancer is, therefore, often diagnosed late, making treatment difficult due to the advanced stage of these tumours. To improve the colorectal cancer detection rate in people with LD, we recommend that the government may have to review the screening age, provide more resources to support them and their caregivers, educate and increase awareness of the risk factors and signs and symptoms of colorectal cancer.